When repair meets chromatin. First in series on chromatin dynamics. - Green, C; Almouzni, G (2002)
In eukaryotic cells, the inheritance of both the DNA sequence and its organization into chromatin is critical to maintain genome stability. This maintenance is challenged by DNA damage. To fully understand how the cell can tolerate genotoxic stress, it is necessary to integrate knowledge of the nature of DNA damage, its detection and its repair within the chromatin environment of a eukaryotic nucleus. The multiplicity of the DNA damage and repair processes, as well as the complex nature of chromatin, have made this issue difficult to tackle. Recent progress in each of these areas enables us to address, both at a molecular and a cellular level, the importance of inter-relationships between them. In this review we revisit the 'access, repair, restore' model, which was proposed to explain how the conserved process of nucleotide excision repair operates within chromatin. Recent studies have identified factors potentially involved in this process and permit refinement of the basic model. Drawing on this model, the chromatin alterations likely to be required during other processes of DNA damage repair, particularly double-strand break repair, are discussed and recently identified candidates that might perform such alterations are highlighted.